2018
DOI: 10.1177/0284185118813709
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after prostatic artery embolization in patients with symptomatic benign prostatic hyperplasia

Abstract: Background Prostatic artery embolization (PAE) has recently been described as a promising alternative treatment for lower urinary tract symptoms (LUTS) due to an enlarged, benign prostate. Purpose To evaluate the safety, morbidity, and functional outcomes after PAE. Material and Methods Twenty-nine consecutive patients were included. All patients had computed tomography angiography before the procedure. Microcatheters were used for selective embolization of the PAs. Large side branches to non-target organs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…Consistent with the findings of previous investigations, 6,1214 our study showed that PAE is an efficacious treatment for LUTS secondary to large prostate volume (>80 mL) in elderly patients (≥80 years of age) who were not suitable candidates for open or endoscopic surgical procedures; notably, we found that this surgical approach had a favorable safety profile. All six of the monitored functional results were significantly improved at 12 months postoperatively in the present study, similar to the results reported by Gao et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the findings of previous investigations, 6,1214 our study showed that PAE is an efficacious treatment for LUTS secondary to large prostate volume (>80 mL) in elderly patients (≥80 years of age) who were not suitable candidates for open or endoscopic surgical procedures; notably, we found that this surgical approach had a favorable safety profile. All six of the monitored functional results were significantly improved at 12 months postoperatively in the present study, similar to the results reported by Gao et al.…”
Section: Discussionsupporting
confidence: 92%
“…PAE was proposed relatively recently and has been the focus of increasing interest in both radiological and urological communities since its first successful use for BPH with acute urinary retention in 2010. 7 Consistent with the findings of previous investigations, 6,[12][13][14] our study showed that PAE is an efficacious treatment for LUTS secondary to large prostate volume (>80 mL) in elderly patients (!80 years of age) who were not suitable candidates for open or endoscopic surgical procedures; notably, we found that this surgical approach had a favorable safety profile. All six of the monitored functional results were significantly improved at 12 months postoperatively in the present study, similar to the results reported by Gao et al 9 Furthermore, Lebdai et al 15 reported a mean reduction in IPSS of 11.9 points at 1 month postoperatively, which persisted at 6 months postoperatively.…”
Section: Discussionsupporting
confidence: 90%
“…A total of 263 articles were removed after reading the abstract. Of the remaining 115 studies assessed for full-text eligibility, 32 studies with a total of 2116 patients (ranging from 11–199) were selected for data extraction [ 5 , 6 , 7 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. A PRISMA flow diagram depicts the process of study selection ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this review, the incidence of urinary tract infections (UTIs) requiring antibiotic treatment as reported by 20 studies was 2.7% (SD 3.7). Seven studies recorded no UTIs and the highest UTI percentage of 13.8% was reported in a study by Kløw et al [ 35 ]. Currently, antibiotic prophylaxis covering Gram-negative rods is routinely administered prior to PAE in most centers, even though no randomized trials evaluating its efficacy exist to date.…”
Section: Discussionmentioning
confidence: 99%